Świat reklamy w „Dzienniku Bydgoskim” w latach 1920-1939 (Kronika Bydgoska, 2015)
Press advertising had gone through many changes in the interwar period. In the beginning, it looked like today’s obituaries. As far as content, there was too much or too little of it. Over time, graphic art had been added along with encouraging messages. In the analyzed advertisements dating from 1920-1939, we can notice the dynamics of changes taking place in the design of advertisements. The author analyzed ads featured in the daily “Dziennik Bydgoski”. For this purpose, the main categories of products advertised were selected. Advertisements were described in terms of their visual impact, content, persuasion and the history of the company that placed them.